Leveraging Silicon Nanowires in Nanotechnology Education to Foster Creative Thinking Among High School Students - Isna, Isnanik Juni Fitriyah; Andik Wahyun Muqoyyidin; Septi Aprilia (Educational Researcher Journal, 2025)
The integration of nanotechnology into education is crucial to fostering creative thinking among high school students in the context of advanced scientific developments. This study aims to explore how the use of silicon nanowires (SiNWs) in nanotechnology education can enhance students' creativity. Using a qualitative descriptive methodology, data were collected through interviews, observations, and focus group discussions involving students and educators. The results indicate that hands-on experiments with SiNWs significantly enhance students' engagement, comprehension of abstract concepts, and creative problem-solving skills. The study highlights the importance of interactive and interdisciplinary approaches in modern science education to nurture innovation and prepare students for future challenges.